Sequence characterized amplified region markers for species-specific identification of three threatened Aquilaria species - Hairul Azman, Roslan; Md. Anowar, Hossain; Nur Qistina, Othman; Tawan, C.S; Ipor, Isa B. (Chiang Mai University, 2017)
Gaharu, a substance that is produced by Aquilaria species, is of economic importance and widely used for the production of incense, medicine and perfume, used all over the world. However, not all Aquilaria trees produce gaharu, thus indiscriminate harvesting from the natural population by gaharu collectors threatens their population greatly. Conservation of these tree species is of the main concern. Nevertheless, it is very difficult and time consuming to differentiate all the gaharu producing species. Here we report on the development of DNA-based molecular markers that is able to distinguish three species of Aquilaria; A. beccariana Teigh., A. malaccensis Lam. and A. microcarpa Baill. Random amplification polymorphic regions (RAPD) were employed to develop polymorphic bands using M13 and OPA10 primers. From these, species-specific bands were determined and selected. Sequence characterized amplified region (SCAR) primers were subsequently designed and tested on several plant species. The M13 primer produced one diagnostic band for each A. beccariana Teigh. (750 bp) and A. microcarpa Baill. (730 bp). Meanwhile, the use of OPA10 primer generated one diagnostic band for all the species with sizes of 350 bp, 450 bp and 2000 bp for A. beccariana Teigh., A. malaccensis Lam. and A. microcarpa Baill., respectively. From these unique RAPD bands, five pairs of sequence characterized amplified region (SCAR) primers were designed and subsequently tested against each other and other species (Cryptocoryne narutoi, C. longcauda, Morinda citrifolia and Amorphophallus hewitti). The SCAR primers were highly species-specific and could be used to rapidly identify the three species of Aquilaria.